Influence Of Website Quality And Augmented Reality To Purchase Intention With Satisfaction As Mediation - Djakasaputra, Arifin; Juliana, Juliana; Pramezwary, Amelda; Lemy, Diena M (SEIKO : Journal of Management & Business, 2023)
Through development technology, exists change method marketing from method conventional become technology. Marketing in a manner digital the more develop, Where all person avoid meeting stare advance And make majority resident Indonesia connected with Internet. Matter This made opportunity for digital marketing For develop in all industrial sectors, including the textile industry in Indonesia. This research is focused in the housing sector. Textile Marketing itself requires a dimensional approach service And product. Website And augmented reality is service digital Which can represent marketing in Textile industry. This research will use SOR theory ( Stimulus – organisms – Responses ). Where website quality etc augmented reality role as stimulus, customer satisfaction acts as an organism and purchase intention plays a role as responses . This study aims to determine the effect of Website quality and Augmented reality on Purchase intention both directly and indirectly (with mediation customers satisfaction ). Study This use method quantitative with questionnaire as tool collection data. Sample study is people Greater Jakarta with minimum age of 19 years and want to have a house in 8 years forward. Through this research it is known that website quality and Augmented reality have no significant effect on purchase intention directly. However, websites quality and Augmented reality have a significant influence on purchase intention by no means direct or with mediation customers satisfaction . Keywords: website Quality, augmented reality, Purchase Intentions